Central bank intervention in the foreign exchange market and interest rate policy in Jamaica : signaling of leaning against the wind - Seerattan, Dave ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2008)
Investigates in a multivariate GARCH framework whether dierect intervention 'signals' the future interest rate policy stance of the Central Bank or whether interest rate policy decisions induce interventions designed to 'lean against the wind' of exchange trends in jamaice.